2022
DOI: 10.32604/cmc.2022.024590
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach Utilizing Binary-View Transformer for Speech Recognition Task

Abstract: The deep learning advancements have greatly improved the performance of speech recognition systems, and most recent systems are based on the Recurrent Neural Network (RNN). Overall, the RNN works fine with the small sequence data, but suffers from the gradient vanishing problem in case of large sequence. The transformer networks have neutralized this issue and have shown state-of-the-art results on sequential or speech-related data. Generally, in speech recognition, the input audio is converted into an image u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The deep neural network is a subfield of AI and directly learns features from the data before making decisions. In numerous fields, including speech recognition [27][28][29][30], image processing [31][32][33][34], natural language processing [35,36], and bioengineering [37], deep learning algorithms have demonstrated that they are the most effective and exceptional machine learning algorithms. Additionally, several studies demonstrated that deep learning algorithms outperform traditional machine learning methods when applied to various complex learning problems [38,39].…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…The deep neural network is a subfield of AI and directly learns features from the data before making decisions. In numerous fields, including speech recognition [27][28][29][30], image processing [31][32][33][34], natural language processing [35,36], and bioengineering [37], deep learning algorithms have demonstrated that they are the most effective and exceptional machine learning algorithms. Additionally, several studies demonstrated that deep learning algorithms outperform traditional machine learning methods when applied to various complex learning problems [38,39].…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…Due to the time serial, RNNs can capture the long-term dependency of the temporal data [7]. Thus, RNNs are the adequate technology for machine translation [8] and speech recognition [9,10]. Meanwhile, RNNs also play an essential role in specific video recognition, such as contextual video recognition [11] and visual sequence tasks [12,13].…”
Section: Introductionmentioning
confidence: 99%